2017
DOI: 10.1002/jbm.a.36200
|View full text |Cite
|
Sign up to set email alerts
|

SPIO‐Au core–shell nanoparticles for promoting osteogenic differentiation of MC3T3‐E1 cells: Concentration‐dependence study

Abstract: This work aims to explore the concentration-dependence of SPIO-Au core-shell NPs (17.3 ± 1.2 nm in diameter) on biocompatibility and osteogenic differentiation of preosteoblast MC3T3-E1 cells. The stability of NPs was first investigated by UV-Vis absorption spectra and zeta potential measurement. Then concentration effects of NPs (1–80 μg/mL) were evaluated on viability, morphology, proliferation, cellular uptake and alkaline phosphate (ALP) activity levels. Results have shown strong stability and no acute tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The present study focused on the effects of miR-135b-5p on osteogenic differentiation and osteoblast proliferation. Therefore, the mouse pre-osteoblast cell line MC3T3-E1, which is widely used in osteogenic differentiation investigation (30)(31)(32), was selected for this study. Osteogenic differentiation was induced in MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present study focused on the effects of miR-135b-5p on osteogenic differentiation and osteoblast proliferation. Therefore, the mouse pre-osteoblast cell line MC3T3-E1, which is widely used in osteogenic differentiation investigation (30)(31)(32), was selected for this study. Osteogenic differentiation was induced in MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…42 Yuan and colleagues reported that gold (Au)coated SPIONs in MC-3T3-E1 cell line can maintain a 97% cell viability for seven consecutive days, showing the excellent biocompatibility. 43 Other studies have shown that nerve growth factor (NGF) functionalized Au coated SPIONs (NGF-SPIO-Au) (0.1-10 μg/mL) also had no toxicity in PC-12 cells after 5 days of incubation. 44 Gupta et al chose Pullulan as the coating material of SPIONs to prepare Pn-SPION.…”
Section: Coatingmentioning
confidence: 99%
“…Coating the surfaces of SPIO NPs with gold may dramatically reduce their toxicity, as well as their cellular uptake. Our previous work demonstrated that citrate anion-capped or NGF-functionalized SPIO-Au core-shell NPs at 21 nm have excellent in vitro cellular viability in the MC-3T3 cell line [32] (viability > 93%, 7 days) and PC-12 cell line [17] (viability > 96%, 5 days) at 10-80 ug/mL dosage levels, without affecting the cell morphology. The cell proliferation rates of both cell lines are also enhanced by SPIO-Au NPs.…”
Section: Toxicity and Cellular Uptake Of Magneto-plasmonic Npsmentioning
confidence: 99%